NKX3.1 Identifies Prostatic Origin of Dural Metastasis in the Setting of Negative Prostate-Specific Antigen Stain. (October 2020) - Shen, Jeffrey Z.; Memon, Adeel A.; Hackney, James R.; Sotoudeh, Houman; Fathallah-Shaykh, Hassan
No clear guidelines exist for the appropriate diagnostic workup of an intracranial mass suspected to be a metastasis from unknown primary origin. Dural metastasis from prostatic origin is very rare. Patients with a known history of metastatic prostate cancer who present with a newly discovered lesion on brain imaging require neurosurgical biopsy to confirm diagnosis prior to initiating treatment. Intracranial metastasis from prostate cancer is rare, and dural metastasis is rarer than intraparenchymal metastasis. Current consensus guidelines support immunohistochemical staining with classic markers such as prostate-specific antigen (PSA) to identify prostatic origin. However, PSA detection of prostate metastases declines with higher Gleason scores and in patients undergoing androgen deprivation therapy. NKX3.1 is another stain that is highly sensitive and specific for prostate. Our patient was a 54-year-old man with a history of metastatic prostate cancer who presented with new-onset seizures. Brain imaging revealed a dural-based lesion with surrounding vasogenic edema and midline shift. The patient underwent resection of the lesion, which was stained with multiple cancer markers. Prostate-specific antigen was negative, but NKX3.1 was positive indicating a prostatic origin for the mass. He underwent a craniectomy to remove the lesion and was given steroids. However, he succumbed to his illness several months later. Here, we document the first report to our knowledge of a patient with prostate metastasis to the dura that is PSA negative, but NKX3.1 positive.